2021
DOI: 10.1111/jzo.12873
|View full text |Cite
|
Sign up to set email alerts
|

Co‐occurrence of high densities of brown hyena and spotted hyena in central Tuli, Botswana

Abstract: Large carnivore populations are declining worldwide due to anthropogenic causes such as habitat loss and human expansion into wild areas. Competition between large carnivores can exacerbate this decline. While brown hyena Parahyaena brunnea and spotted hyena Crocuta crocuta belong to the same family, they are rarely found in the same area or co-occur at low densities as spotted hyena are known to exclude brown hyena. In Central Tuli, Botswana, however, brown hyena and spotted hyena are both found at high densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 48 publications
2
24
4
Order By: Relevance
“…In addition, temporal overlap was not significantly affected by body size ratio. Our results fail to demonstrate low temporal overlap and actually found high temporal overlap between smaller and larger carnivore species (Ramesh et al 2017, Miller et al 2018, Chaudhary et al 2020, Vissia et al 2021). These results suggest that subordinate carnivores avoid dominant carnivores in space but not in time.…”
Section: Discussioncontrasting
confidence: 76%
“…In addition, temporal overlap was not significantly affected by body size ratio. Our results fail to demonstrate low temporal overlap and actually found high temporal overlap between smaller and larger carnivore species (Ramesh et al 2017, Miller et al 2018, Chaudhary et al 2020, Vissia et al 2021). These results suggest that subordinate carnivores avoid dominant carnivores in space but not in time.…”
Section: Discussioncontrasting
confidence: 76%
“…The estimate of 0.219 spotted hyaenas per 100 km 2 was much lower than previous studies in similar environments such as the Ngamiland District (Rich et al, 2019) and central Tuli, Botswana (Vissia et al, 2021), but similar to estimates from farmlands in the Tsauchab River Valley, Namibia (Fouché et al, 2020; Fig. 2).…”
Section: Discussionsupporting
confidence: 61%
“…2). The highest recorded densities are from reserves in Namibia (Okonjima Nature Reserve; Edwards et al, 2019), South Africa (Kwandwe Nature Reserve; Welch & Parker, 2016), and the central Tuli block, Botswana (Vissia et al, 2021). These far exceed our density estimate (Supplementary Table 2), although assumptions about fence permeability may account for some of these differences (Williams et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with other studies that reported brown hyaena success to be negatively impacted by the presence of spotted hyaenas due to kleptoparasitism and direct mortality (Mills, 1990; Mills & Mills, 1982; Williams et al, 2020). However, recent research from Central Tuli, Botswana—a more comparable environment to the BVC than the formerly mentioned study areas—found high densities of both spotted and brown hyaenas (Vissia et al, 2021). This finding was attributed to high prey densities in the area, which is also a feature of the BVC, and may similarly explain why the prevalence of brown hyaenas was not negatively affected by lions or spotted hyaenas in our study.…”
Section: Discussionmentioning
confidence: 75%